Trust and the Unintended Effects of Behavior Control in Virtual Teams1 - Piccoli, Gabriele; Ives, Blake (MIS Quarterly, 2003)
This article reports the findings of a longitudinal study of temporary virtual teams and explores the role of behavior control on trust decline. We conducted an experiment involving 51 temporary virtual teams. Half of the teams were required to comply with behavior control mechanisms traditionally used in colocated teams. Their counterparts were allowed to self-direct. Our analysis shows that the behavior control mechanisms typically used in traditional teams have a significant negative effect on trust in virtual teams. In-depth analysis of the communication logs of selected teams reveals that trust decline in virtual teams is rooted in instances of reneging and incongruence. Behavior control mechanisms increase vigilance and make instances when individuals perceive team members to have failed to uphold their obligations (i.e., reneging and incongruence) salient. Heightened vigilance and salience increase the likelihood that team members’ failure to fulfill their obligations will be detected, thus contributing to trust decline.